2020
DOI: 10.1128/jvi.00167-20
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Glycoprotein-Initiated Signaling Mediates the Aberrant Activation of Akt

Abstract: Human cytomegalovirus (HCMV) is a major cause of morbidity and mortality among immunocompromised and immunonaive individuals. HCMV-induced signaling initiated during viral entry stimulates a rapid noncanonical activation of Akt to drive the differentiation of short-lived monocytes into long-lived macrophages, which is essential for viral dissemination and persistence. We found that HCMV glycoproteins gB and gH directly bind and activate cellular epidermal growth factor receptor (EGFR) and integrin β1, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 96 publications
(177 reference statements)
1
19
0
Order By: Relevance
“…Activation of AKT induced by gB has also been demonstrated to promote monocytes survival [295,296]. Specifically, gB has been shown to act in tandem with HCMV glycoprotein H (gH) leading to atypical activation of Akt which ultimately leads to inhibition of apoptosis (Figure 5).…”
Section: Human Cytomegalovirus (Hcmv)mentioning
confidence: 99%
“…Activation of AKT induced by gB has also been demonstrated to promote monocytes survival [295,296]. Specifically, gB has been shown to act in tandem with HCMV glycoprotein H (gH) leading to atypical activation of Akt which ultimately leads to inhibition of apoptosis (Figure 5).…”
Section: Human Cytomegalovirus (Hcmv)mentioning
confidence: 99%
“…The simultaneous activation of EGFR and integrin β1 results in noncanonical activation of AKT signaling. Lastly, inhibition of SHIP was shown to downregulate the pro-survival proteins Mcl-1 and HSP27 [ 159 ]. This contrasts with its normal inhibitory function [ 154 ]; however, aberrant SHIP function has been previously demonstrated in cancer cells [ 160 ].…”
Section: Autophagy and Apoptosismentioning
confidence: 99%
“…In monocytes, the binding of HCMV gB to epidermal growth factor receptor (EGFR), as well as the binding of the viral pentameric complex to integrins, drives signaling through phosphatidylinositol 3-kinase (PI3K) and mTOR kinase that leads to the upregulation of MCL-1 ( 18 ). The virus, after 48 h of infection, shifts from MCL-1 to Bcl-2 as the primary antiapoptotic tool, and the upregulation of Bcl-2 is mediated by integrin signaling events following initial viral binding ( 19 ). In CD34 + HPCs, Reeves et al showed that MCL-1 is upregulated via gB stimulation of mitogen-activated protein kinase (MAPK) signaling in the absence of de novo viral gene expression ( 20 ).…”
Section: Introductionmentioning
confidence: 99%